Efficacy and safety of ribavirin therapy for chronic hepatitis E after kidney transplantation. Issue 10 (30th May 2019) - Yoshida, Tomoaki; Takamura, Masaaki; Goto, Ryo; Takeuchi, Suguru; Tsuchiya, Atsunori; Kamimura, Kenya; Tasaki, Masayuki; Nakagawa, Yuki; Saito, Kazuhide; Tomita, Yoshihiko; Terai, Shuji
Abstract : Hepatitis E virus (HEV) infection has been recognized as an acute condition. However, recent reports have shown that immunocompromised patients, such as those receiving solid‐organ transplantation, can develop chronic hepatitis with HEV infection. We report two cases of chronic hepatitis E after kidney transplantation (KT) who were successfully treated with ribavirin monotherapy. Several years after KT, both patients had sustained elevations in the levels of liver enzymes for a period of more than 6 months. Both patients had HEV infection, genotype 3a. Histological studies showed infiltration of inflammatory cells without fibrosis. Treatment included ribavirin monotherapy at a dosage of 600 mg daily for 3 months. One month after therapy initiation, HEV‐RNA turned to negative, and remained negative at 24 weeks after ribavirin therapy without severe complications. Although the treatment of chronic hepatitis E is not fully established, ribavirin therapy can be a safe and effective treatment for chronic hepatitis E.